Rodents and pathogens distribution along an altitudinal gradient in the Italian Alps - Tagliapietra, V.; Cagnacci, F.; Devineau, O.; Girardi, M.; Rosso, F.; Arnoldi, D.; Ferrari, G. (2023)
In a global change context, the association between generalists and specialists could be a determinant of ecosystem stability. This holds particularly true in mountain ecosystems, where the environmental tolerance of generalists to global warming may lead to their upward distributional shifts, while a decline is expected in specialists. As a consequence, even the parasites that these species carry can shift, eventually promoting the emergence of infectious diseases in newly colonized areas. We examined these relationships in small mammals along an altitudinal gradient in the Italian Alps (Province of Trento), where we identified 5 altitudinal belts from 500 to 2500 m a.s.l. with 500-meter intervals. We live-trapped small mammals applying capture-mark-recapture technique in 2019 and 2020. We counted ticks on rodents and collected blood and ear biopsy samples. Molecular PCR based methods coupled with sequencing and serological assays were performed for vector- and rodent-borne pathogens screening. We analysed probability of infection with Generalized Linear Mixed Models . Overall, we captured 333 animals belonging to 11 species (Apodemus flavicollis, A. sylvaticus, Chionomys nivalis, Microtus arvalis, M. subterraneus, M. agrestis, Myodes glareolus, Sorex araneus, S. alpinus, S. minutus, Crocidura leucodon). Apodemus spp. and My. glareolus were sympatric in the montane belt, from 500 to 1500 m a.s.l. My. glareolus was also present in the alpine belts, from 2000 to 2500 m, together with C. nivalis, Microtus spp. and shrews. We counted 3782 feeding-ticks belonging to the genus Ixodes. From the molecular screening of 324 ear samples we detected an unevenly altitudinal pattern of tick-borne pathogens distributions , with Borrelia spp. occurring up to 1500 m a.s.l. (prevalence 13.88%), while Anaplasma phagocytophilum (7.09%) and Babesia microti (3.08%) mainly recorded in alpine belts. We screened 440 sera samples and detected Dobrava virus in A. flavicollis (0.8%). Also 10% C. nivalis tested positive to both ...